(untitled) (Altre Modernità, 2025)
The aim of this paper is to provide an overview of the tourism communication abroad produced by Italian institutions between 1919 and 1945, placing it in the historical and political context in which it was created. In particular, the paper describes the research of documentary and textual sources (brochures, magazines, etc.) carried out in the archives of ENIT and the ministerial institutions of the Fascist regime that supervised the tourism sector. Through the analysis of the documentation found and the literature review, the central institutional organisation of the Italian tourism sector in the inter-war period will be summarized. In addition, the work carried out by ENIT abroad in the field of tourism publications will be examined, with reference to quantitative data available. Particular attention will be paid to ENIT’s promotional activities in English-speaking countries, highlighting how the institution gradually began to address the British and American public in different ways.